2011
DOI: 10.1016/j.yhbeh.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Does access to the bluestreak cleaner wrasse Labroides dimidiatus affect indicators of stress and health in resident reef fishes in the Red Sea?

Abstract: Interactions between the bluestreak cleaner wrasse Labroides dimidiatus and its client reef fish are a textbook example of interspecific mutualism. The fact that clients actively visit cleaners and invite inspection, together with evidence that cleaners eat many client ectoparasites per day, indeed strongly suggests a mutualistic relationship. What remains unknown is how parasite removal affects the physiology of clients and thereby their body condition, health, and immune function. Here we addressed these iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…To collect blood, individuals from both groups were anesthetized by placing them in an aerated bucket with a solution of MS-222 in seawater ( tricaine methanesulfonate , Sigma-Aldrich ; dilution 1:10,000). Aft er about 1 min, fi sh reached a deep stage of anesthesia 28,34 . A sample of 50 μ l of blood was taken from the caudal vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To collect blood, individuals from both groups were anesthetized by placing them in an aerated bucket with a solution of MS-222 in seawater ( tricaine methanesulfonate , Sigma-Aldrich ; dilution 1:10,000). Aft er about 1 min, fi sh reached a deep stage of anesthesia 28,34 . A sample of 50 μ l of blood was taken from the caudal vein.…”
Section: Methodsmentioning
confidence: 99%
“…Based on research demonstrating health benefi ts of physical contact in humans 5 -8 , we assumed that similar benefi ts to clients should also be measurable at the physiological level. As interactions with cleaners aff ect the stress axis and immune activity of clients 27,28 , we asked whether physical contact alone, without the additional benefi t of parasite removal, could contribute to a change in client stress levels, namely causing cortisol levels to decline. Twice a day, for a period of 10 days, we provided to captive surgeonfi sh, which are frequent visitors to cleaning stations in the wild 22 , access to a model cleanerfi sh, which had a soft brush on its ventral side.…”
mentioning
confidence: 99%
“…Whether cleaners affect the parasite load of small species remains unclear. Clients with natural cleaner access had higher body condition and a lower antibody response than those without, suggesting that cleaner access decreases the need for active immunity, releasing resources allocated to somatic growth [9]. Cleaner absence for 8.5 years reduced fish length in two damselfishes, but fish growth was not measured [10].…”
Section: Introductionmentioning
confidence: 97%
“…removing the ectoparasites or gaining physical stimulation. Recent research has demonstrated that clients that interact more frequently with cleaners have better body condition [37] and the recurrent physical contacts contribute to reducing their stress levels [38]. The level of benefit arising from these interactions depends on ability of client fish to identify the specific cues to safely approach the fish providing an honest, fair cleaning service and avoid dubious cues, such as those coming from “false” or mimic cleaners.…”
Section: Introductionmentioning
confidence: 99%